Carotid Body Baroreceptor Preservation and Control of Arterial Pressure in Eversion Carotid Endarterectomy - Kotsis, Thomas; Christoforou, Panagitsa; Nastos, Konstantinos (International Journal of Angiology, 2020)
The technique of the eversion carotid endarterectomy (ECEA), as an alternative to the conventional endarterectomy with primary or patch angioplasty, is an established technique for managing internal carotid artery stenoses and recently its application has been upgraded through the European Society for Vascular Surgery guidelines (Recommendation 55: Class 1, Level A). However, the typical eversion method has been associated with postoperative hypertension due to loss of the baroreceptor reflex; the standard oblique transection at the bulb performed in the eversion endarterectomy interrupts either the baroreceptor sensoring tissue, which is mostly located in the adventitia at the medial portion of the proximal internal carotid artery, or even the proper Hering nerve, a branch of the glossopharyngeal nerve. These actions deregulate the natural negative feedback of the carotid baroreceptor. Guided by the anatomical location of the baroreceptor sensor we have elaborated a slight modification of the classical ECEA to maintain as much as possible of the viable carotid baroreceptor sensoring surface. By extending the oblique incision distal to the carotid bifurcation in the medial part of the internal carotid artery stem, an eyebrow-like part of the proximal internal carotid artery is maintained and the axis from the sensoring tissue to the nerve of Hering is protected and following the endarterectomy, postoperative arterial blood pressure levels are lower than in the classical ECEA due to the maintenance of the efficiency of the baroreceptor reflex. During the period from September 2016 to November 2018, carotid endarterectomy was performed in 57 patients. Twenty-eight of them underwent the typical ECEA and 29 patients had the modified eyebrow eversion carotid endarterectomy (me-ECEA). The changes of blood pressure baseline during the postoperative course in ECEA and me-ECEA group were analyzed and compared. Postoperative hypertension was defined as an elevation of systolic blood pressure (SBP) greater than 140 mm Hg. Patients who underwent typical ECEA had significantly higher postoperative blood pressure values compared with those who underwent me-ECEA. Actually, the mean postoperative SBP was 172.67 ± 24.59 mm Hg in the typical ECEA group compared with 160.86 ± 12.83 mm Hg in the me-ECEA group (p = 0.023). The mean diastolic blood pressure in the ECEA group was 65.42 ± 11.39 mm Hg compared with 58.06 ± 9.06 mm Hg in the me-ECEA group (p = 0.009). Our proposed me-ECEA technique seems to be related to lower rates of postoperative hypertension compared with the typical ECEA, probably due to the sparing of the main mass of the baroreceptor apparatus; this improved modification (me-ECEA) of the typical eversion procedure could represent an alternative ECEA technique with its inherent advantages.
Keywords: baroreceptor; carotid body; eversion carotid endarterectomy; modified ECEA; post carotid endarterectomy hypertension; blood pressure